2007
DOI: 10.4314/sajas.v35i3.4053
|View full text |Cite
|
Sign up to set email alerts
|

The effect of feeding rosemary, oregano, saffron and &#945-tocopheryl acetate on hen performance and oxidative stability of eggs

Abstract: In this study the effects of feeding rosemary, oregano, saffron and α-tocopheryl acetate on hen performance and egg quality were investigated. One hundred-twenty Lohmann laying hens, 32 weeks old, were divided into five groups replicated four times with six hens per replicate. One group was given a basal diet and served as control (CON). The experimental diets given to the other four groups were based on the basal diet but contained an additional 200 mg α-tocopheryl acetate/kg (TOC), or rosemary at 5 g/kg diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
64
4
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(99 citation statements)
references
References 36 publications
(46 reference statements)
7
64
4
9
Order By: Relevance
“…This was fully in agreement with earlier research findings, which indicated that phenolic compounds of plants from the Labiate family improved the oxidative stability of poultry meat (Lopez-Bote et al, 1998;Botsoglou et al, 2002Botsoglou et al, , 2005Basmacıoğlu et al, 2004). The marked increase in L* value in chicken meat is closely related to total antioxidant capacity because of the relationship between brightness of meat (L* value) and phospholipase A 2 activity, an enzyme that oxidases phospholipids in meat (Soares et al, 2003).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This was fully in agreement with earlier research findings, which indicated that phenolic compounds of plants from the Labiate family improved the oxidative stability of poultry meat (Lopez-Bote et al, 1998;Botsoglou et al, 2002Botsoglou et al, , 2005Basmacıoğlu et al, 2004). The marked increase in L* value in chicken meat is closely related to total antioxidant capacity because of the relationship between brightness of meat (L* value) and phospholipase A 2 activity, an enzyme that oxidases phospholipids in meat (Soares et al, 2003).…”
Section: Discussionsupporting
confidence: 82%
“…Phytogenic compounds that were tested, which are mostly consisted of phenolic compounds, include rosemary and sage extracts (Lopez-Bote et al, 1998), oregano and oregano oil (Botsoglou et al, 2002;, rosemary (Govaris et al, 2004), and rosemary and oregano oil (Basmacıoğlu et al, 2004;Botsoglou et al, 2005). However, there were no indications of significant beneficial effects of phytoadditive compounds on carcass yield and carcass cut-up parts yield (Alçiçek et al, 2004;Jamroz et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…As regards eggshell thickness higher doses of thyme and oregano oils (1 ml kg -1 ) in feed mixture had positive effect (P >0.05). Similar findings to previous study found Botsoglou et al (2005). Park et al (2015) presented eggshell thickness of layers in the range from 0.37 to 0.40 mm.…”
Section: Resultssupporting
confidence: 81%
“…Likewise, the active compounds of rosemary (such as carnosol and carnosic acid) are capable of terminating free-radical reactions and scavenging reactive oxygen species (Sánchez-Escalante et al, 2001), preventing the oxidation of yolk fatty acids, as these antioxidant compounds can be transferred from the hen's diet to the egg (Botsoglou et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the antioxidant compounds found in rosemary can be transferred to eggs through the hen's diet, as detected by Botsoglou et al (2005), who evaluated the inclusion of rosemary (5g kg ) extracts in the diets of laying hens.…”
Section: Introductionmentioning
confidence: 99%